2001
DOI: 10.1097/00005721-200105000-00014
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of EARLY PREGNANCY LOSS on Adolescents

Abstract: Adolescents who experience early pregnancy loss may have significant physical, emotional, social, and cognitive grief responses and may be at risk for depressive symptoms. Nurses should assess adolescents' responses to early pregnancy loss and provide sensitive nursing care. Discharge planning should include verbal and written information on the bereavement process and grief responses, anticipatory guidance, when and how to access health care, and referral as appropriate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 12 publications
0
15
0
1
Order By: Relevance
“…Some found little or no significance in the event and experienced a limited grief reaction. Others still considered the event significant and were affected by it in several areas of their lives even months or years after the miscarriage occurred ( Bansen & Stevens, 1992 ;Barglow et al, 1973 ;Cordle & Prettyman, 1994 ;Corney & Horton, 1972 ;Goldbach et al, 1991 ;Horowitz, 1978 ;Hutti, 1992 ;Hutti et al, 1998 ;Madden, 1988Madden, , 1994Neugebauer et al, 1992Neugebauer et al, , 1997Robinson et al, 1994 ;Smart, 2003 ;Thomas & Striegel, 1994-1995Wheeler, 1997aWheeler, , 1997bWheeler & Austin, 2001 ). Sanders's (1999) Integrative Theory of Bereavement proved to serve as an adequate representation of grief responses after an early pregnancy loss.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some found little or no significance in the event and experienced a limited grief reaction. Others still considered the event significant and were affected by it in several areas of their lives even months or years after the miscarriage occurred ( Bansen & Stevens, 1992 ;Barglow et al, 1973 ;Cordle & Prettyman, 1994 ;Corney & Horton, 1972 ;Goldbach et al, 1991 ;Horowitz, 1978 ;Hutti, 1992 ;Hutti et al, 1998 ;Madden, 1988Madden, , 1994Neugebauer et al, 1992Neugebauer et al, , 1997Robinson et al, 1994 ;Smart, 2003 ;Thomas & Striegel, 1994-1995Wheeler, 1997aWheeler, , 1997bWheeler & Austin, 2001 ). Sanders's (1999) Integrative Theory of Bereavement proved to serve as an adequate representation of grief responses after an early pregnancy loss.…”
Section: Discussionmentioning
confidence: 99%
“…Research has shown that pregnancy loss can evoke feelings of grief that are dealt with in much the same way as other types of loss ( Bansen & Stevens, 1992 ;Barglow et al, 1973 ;Cecil, 1994aCecil, , 1994bCordle & Prettyman, 1994 ;Corney & Horton, 1972 ;Goldbach, Dunn, Toedter, & Lasker, 1991 ;Horowitz, 1978 ;Hutti, 1992 ;Hutti, de Pacheco, & Smith, 1998 ;Janssen, Cuisinier, de Graauw, & Hoogduin, 1996Madden, 1988Madden, , 1994Neugebauer et al, 1992 ;Neugebauer et al, 1997 ;Robinson, Stirtzinger, Stewart, & Ralevski, 1994 ;Smart, 2003 ;Thomas & Striegel, 1994-1995Wheeler, 1997aWheeler, , 1997bWheeler & Austin, 2001 ). Those in grief often experience fairly well-defined phases that hopefully culminate in a healthy integration of the loss into the tapestry of their life.…”
Section: Grief Analysis Frameworkmentioning
confidence: 99%
“…Groups have been employed with adolescents to address a variety of issues, including school dropout (Levinsky & McAleer, 2005), depression (Malekoff, 2004), pregnancy loss (Wheeler & Austin, 2001), and substance abuse (Baez, 2003). Groups can provide an environment that promotes resilience which acts as a protective factor against the physical, emotional, social, and cognitive grief responses of adolescents.…”
Section: Group Therapymentioning
confidence: 99%
“…It was initially developed to measure the physical, emotional, social, and cognitive grief responses to loss among adolescent girls who experienced perinatal or early pregnancy loss (Wheeler & Austin, 2000). The LRL is also sensitive to adolescents who have experienced losses to include the death of a parent, other family member, a friend or peer, or significant other (Wheeler & Austin, 2000 (Wheeler & Austin, 2001). Construct validity is supported for physical, emotional, social, and cognitive grief responses as found in two studies of adolescent girls who had experienced a pregnancy loss (Wheeler & Austin, 2000;Wheeler & Austin, 2001).…”
Section: Quantitative Instrumentationmentioning
confidence: 99%
“…Adolescents may find it more difficult to grieve. The easier solution is for adolescents to become pregnant again; many adolescents purposely become pregnant after their perinatal loss as a way of replacing their baby (Horowitz 1978;Smith et al 1984;Wheeler and Austin 2001). Adolescents need to replace risk taking behaviors with their protective factors which can help them cope with their perinatal loss.…”
Section: Anticipatory Guidance Related To Emotional Strengths Enviromentioning
confidence: 99%